Human Intestinal Barrier Function in Health and Disease. Issue 10 (October 2016) - König, Julia; Wells, Jerry; Cani, Patrice D; García‐Ródenas, Clara L; MacDonald, Tom; Mercenier, Annick; Whyte, Jacqueline; Troost, Freddy; Brummer, Robert‐Jan
Abstract : N/A: The gastrointestinal tract consists of an enormous surface area that is optimized to efficiently absorb nutrients, water, and electrolytes from food. At the same time, it needs to provide a tight barrier against the ingress of harmful substances, and protect against a reaction to omnipresent harmless compounds. A dysfunctional intestinal barrier is associated with various diseases and disorders. In this review, the role of intestinal permeability in common disorders such as infections with intestinal pathogens, inflammatory bowel disease, irritable bowel syndrome, obesity, celiac disease, non‐celiac gluten sensitivity, and food allergies will be discussed. In addition, the effect of the frequently prescribed drugs proton pump inhibitors and non‐steroidal anti‐inflammatory drugs on intestinal permeability, as well as commonly used methods to assess barrier function will be reviewed.